Crawl stroke body dynamics in male champions - Rushall, B. S.; Sprigings, E. J.; Cappaert, J.; King, H. A. (Swimming Science Bulletin)
Five stroking sequences from four male events were filmed during winning performances at either the 1991 World Championships or 1992 Olympic Games. There have been analysed 1.Keiren Perkins at 40 m into his gold medal 1500 m performance at Barcelona. 2.Keiren Perkins at 1440 m into his gold medal 1500 m performance at Barcelona. 3.Evgenyi Sadovyi at 140 m into his gold medal 200 m performance at Barcelona. 4.Alexandre Popov at 40 m into his gold medal 100 m performance at Barcelona. 5.Joerg Hoffman in the mid-stage of his gold medal 1500 m performance at Perth. for body angles and movements, head angles and movements, leg and foot positions and movements, and body rotations. Features analyzed were: (a) angle of the body relative to the horizontal plane, (b) angle of the central axis of the head relative to the horizontal plane, (c) extent of movement of the legs and positions of the feet, and (d) rolling motions of the hips and shoulders. It was found that the body and head in all Ss oscillated vertically to varying degrees, foot and leg positions were often in non-propulsive positions, and the hips and shoulders seldom moved in unison. The effects of these factors on propelling economy and streamline were discussed. Cautious suggestions for improvements were made. It was suggested that even these champions were not as efficient as they could be. All Ss appear to be able to improve streamlining. The magnitude of those possibilities is greater in some than in others. Beneficial changes could be derived from any or all of the following. a.Keeping the body horizontal and not raising the shoulders in concert with arm entries. The body should only be rotated on a horizontal, longitudinal axis. b.Keeping the head down, looking at the bottom and then to the side of the pool when breathing, so that rotation on a horizontal, longitudinal axis is achieved. It is detrimental to streamlining to look forward and/or to raise the head at any time, particularly when breathing. c.Keeping the legs and kick within the body shadow so that form resistance is minimized. The only time the legs should emerge from the position of maximum streamline is when detrimental effects are more than offset by arm-propulsion gains. d.Reducing downward pressure after the arms enter the water and achieving a horizontal pull component earlier. Bending at the elbow, immediately after entry, would assist in faster directional force change. If this could be achieved, there is every likelihood that streamlining will be better maintained. e.Rotating the hips and shoulders together to the same degree in a streamlined position. This will reduce form resistance. f.Allowing the kick to rotate on a longitudinal axis in concert with hip rotation. A concentration on vertical kicking increases form resistance whereas rotation has the potential to decrease it without any loss in propulsion. g.Aligning the upper arm of the pull and recovery with the line of the shoulders to increase the musculature used to generate force as well as maintain the integrity of the shoulder joint. An emphasis on, and tolerance of, internal rotator muscle group activity will eventually cause problems. This proposal will introduce a greater role for the external rotator muscles during the pull. h.Maintaining streamlined feet when kicking so that drag is not created. However, it must be realized that a "braking" action may be a corrective movement for some other error.